Henry B. Stanton correspondence - Stanton, Henry B. (Henry Brewster), 1805-1887.
Correspondence relating to national politics, the presidential inaugurations of Franklin Pierce (1853) and James Buchanan (1857), and to Stanton's official concerns as New York state senator. Correspondents include Charles Levi Woodbury.
Journalist, lawyer, reformer, and New York state legislator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Buchanan, James, -- 1791-1868 -- Inauguration, 1857.; Pierce, Franklin, -- 1804-1869 -- Inauguration, 1853.; Woodbury, Charles Levi, -- 1820-1898 -- Correspondence; New York (State) -- Politics and government -- 1775-1865.; United States -- Politics and government -- 1853-1857.; Journalists; Lawyers; Legislators -- New York (State); Reformers